(untitled) (Raparin Journal of Humanities (RJH), 2024)
Islam’s view of women and their rights is a multifaceted view. Islam’s view of women includes all their aspects and roles, therefore respecting their rights in society as human beings also as a mother, a sister and as a daughter. For each of these women’s status (human being, mother, sister, girl), Islam assigned the rights and fair duties to them and saved them from the oppression of ignorance that has been done to them. Islam also has raised their status and given them the right to participate in building society and improving their levels and abilities. The ruling on women working outside the home is one of the issues that is debated in Islamic centres, Jurisprudence and religious centres have conducted detailed research in this area. If we look at human society today, we see that many women have proved their skills in their work and expertise. They have an active partnership in the development of societies in all areas, even some of those areas that cannot be done without women and without women’s participation are close to disability and immobility. At the same time, the work of women in societies has created some problems for society, and women themselves have increased their obligations because of their work and has caused some social problems, including increased crisis and delay in marriage as well as some crimes and other problems. This research aims to discuss the ruling on women working outside the home and determine the conditions and guidelines of this issue and the appropriate places that exist for women to work and the impact of women’s work in the economic development of countries and societies. It raises all these from the perspective of Islamic jurisprudence.